MENGINTEGRASIKAN PEMBELAJARAN SOSIAL DAN EMOSIONAL UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA DI KELAS - Karisma Tiku Allo; Sariawan, Irianto Sara, Erniati Marampa’ (Adisam Publisher, 2025)
Education is not only about mastery of academic material, but also about the development of social and emotional skills that are essential for life success. One of one important aspect in students' development is their self-confidence. This study aims to explore the effect of integratin social and emotional learning on improving students' self-confidence in the classroom. The research method used is qualitative and literature study. During the research period, learning approaches that integrate social and emotional aspects, such as group work, self-reflection, and problem solving, were applied in daily learning. Problem solving, were applied in daily learning. The results of the study showed a significant increase in students' self- confidence level after the implementation of the integrated learning approach. Students showed improvement in their ability to overcome challenges, confidence in communication, and confidence in their academic abilities. These findings support the importance of integrating social and emotional learning in the curriculum to promote students' holistic development. Implication of this study is the need for a holistic and integrated learning approach in supporting students' confidence development in the classroom. This research contributes to the practical and theoretical understanding of the influence of social and emotional learning on students' self-confidence. This study contributes to the practical and theoretical understanding of the influence of social and emotional learning on students' self- confidence. Further studies can explore more specific and effective strategies in integrating social and emotional aspects in learning to improve students' confidence more broadly.